Pharmacokinetics and Safety of Letermovir and Midazolam Coadministration in Healthy Subjects - Kropeit, Dirk; McCormick, David; Erb‐Zohar, Katharina; Stobernack, Hans‐Peter; Zimmermann, Holger; Rübsamen‐Schaeff, Helga (Clinical pharmacology in drug development, 2022)
Letermovir is a human cytomegalovirus (CMV) terminase inhibitor for the prophylaxis of CMV infection and disease in allogeneic hematopoietic stem‐cell transplant recipients. In vitro studies have identified letermovir as a potential cytochrome P450 (CYP) 3A inhibitor. Thus, the effect of letermovir on the CYP3A isoenzyme‐specific probe drug midazolam was investigated in a phase 1 trial. Healthy female subjects received single‐dose intravenous (IV; 1 mg) and oral (2 mg) midazolam on days –4 and –2, respectively. Letermovir 240 mg once daily was administered on days 1 to 6, and further single doses of midazolam 1 mg IV and oral midazolam 2 mg were administered on days 4 and 6, respectively. Pharmacokinetics, tolerability, and safety were monitored throughout the trial. Following coadministration with letermovir, the least square means ratio for maximum plasma concentration and area under the plasma concentration–time curve from time 0 to the last measurable concentration was 172.4% and 225.3%, respectively, for oral midazolam, and 105.2% and 146.6%, respectively, for midazolam IV. The area under the plasma concentration–time curve from time 0 to the last measurable concentration ratio of midazolam to 1‐hydroxymidazolam increased slightly in the presence of letermovir following IV (8.8‐13.1; 49% increase) and oral (3.3‐5.3; 59% increase) midazolam. Letermovir reached steady state, on average, by days 5 to 6. All treatments were generally well tolerated. Letermovir demonstrated moderate CYP3A inhibition.